Faktor-Faktor yang Mempengaruhi Pendapatan Pedagang Kaki Lima Kecamatan Kartasura Kabupaten Sukoharjo - Hidup Marsudi; Wening Nalurita (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
The research objective was to determine the effect of education and capital on the income of street vendors in Kartasura District, Sukoharjo Regency, either partially or simultaneously. The sample of this research is 100 respondents. The sampling technique uses accidental sampling. Data collection techniques using a questionnaire. The analytical tools used were instrument test (validity test, reliability test), classical assumptions (normality test, multicollinearity and heteroscedasticity test), hypothesis test (multiple linear regression analysis, t test, F test and coefficient of determination test (R2).The results of this study were obtained Education has a significant effect on the income of street vendors in Kartasura District, Sukoharjo Regency, Capital has a significant effect on the income of street vendors in Kartasura District, Sukoharjo Regency.